Floating Photovoltaic Systems in Italy: Challenges and Future Prospects in an Uncertain Regulatory Framework - Tedioli Francesco (EU agrarian Law)
In recent years, floating photovoltaics (FPV) has emerged as a highly promising solution for integrating renewable energy production into the global energy landscape. This innovative technology involves the installation of solar panels on floating platforms, offering a number of advantages over traditional land-based photovoltaic systems. First and foremost FPV enables the use of existing water surfaces, such as artificial reservoirs, lakes, and basins, thereby overcoming limitations related to the availability of agricultural or urban land. This feature is particularly pertinent in geographic contexts characterised by high population density and limited land availability, as is the case in many regions of Italy. Furthermore, floating photovoltaics offer a number of additional environmental benefits. The shading effect of the solar panels on the water surface significantly reduces evaporation, thereby preserving a valuable resource like freshwater, which is particularly important in areas prone to drought. Additionally, the natural cooling effect of the water enhances the efficiency of the photovoltaic panels, increasing the production of electricity.